The expectations of lecturers and employers towards work-integrated learning in the fields of hospitality and tourism education - Sasipha Kanta; Krissana Kiddee; Thanin Ratanaolarn (Humanities, Arts and Social Sciences Studies, 2024)
Work-Integrated Learning (WIL) is an instructional method that integrates the requirements of the employment sector into curriculum design, blending academic and practical training. The key drivers of this type of learning management are lecturers and employers. This study aims to compare expectations in WIL, classified by occupation and work experience. Data were collected from two groups of stakeholders, including lecturers from six higher education institutes using WIL learning management, and supervisors responsible for overseeing learners during their practical training period in the hospitality and tourism field. Fieldwork was conducted with employers in managerial positions at nine hotels in Thailand, using cluster random sampling to obtain the 19 participants. The research instrument was an assessment form evaluating the performance expected of learners upon graduation. The statistics used to analyze the data included mean ( ), standard deviation (SD), and two-way analysis of variance (ANOVA). The findings indicate that lecturers and employers have the highest expectations for WIL learning in the hospitality and tourism field ( = 4.63, SD = 0.27), with different occupations and experiences having similar expectations for WIL learning. These results offer new insights into identifying stakeholder groups as informants for data collection and need analysis in designing or improving curricula. Additionally, the findings can guide curriculum developers in selecting main stakeholders for data collection and need analysis used in curriculum design.
Keywords: Higher Education and Employability; Competency Development and Evaluation; Hospitality and Tourism Education